Systematic review: ileoanal pouch microbiota in health and disease. Issue 4 (5th December 2017) - Segal, J. P.; Oke, S.; Hold, G. L.; Clark, S. K.; Faiz, O. D.; Hart, A. L.
Summary: Background: The resident gut microbiota is essential for physiological processes; the disturbance of its balance is linked to intestinal inflammation. The ileoanal pouch is a model for the study of intestinal inflammation, as inflammation of the pouch is common and mostly develops within 12 months following ileostomy closure. This allows the longitudinal study of the microbiota, giving insight into the microbiota changes during transition from a normal to an inflamed pouch. Aim: To explore the literature on the microbiota of the ileoanal pouch in health and disease. Methods: A systematic computer search of the on‐line bibliographic databases MEDLINE and EMBASE was performed between 1966 and February 2017. Randomised controlled trials, cohort studies and observational studies were included. Studies were included if they reported microbiota analysis on faecal samples or tissue from the ileoanal pouch. Results: Twenty‐six papers were eligible. Following ileostomy closure, anaerobic bacteria are the abundant species in the ileoanal pouch with presence of a diverse microbiota key to maintaining a healthy ileoanal pouch. Acute pouchitis is associated with an increase in Clostridia species, while chronic pouchitis is associated with an increase in Staphylococcus aureus . In the treatment of pouchitis, a decrease in Clostridia species appears to be associated with treatment response. Conclusion: The microbiota plays an important role in both the inflamed and the healthy ileoanal pouch. A direct causal relationship between individual microbiota changes and inflammation has not yet been established, but manipulation of the ileoanal pouch microbiota may be a novel therapeutic avenue to explore.